Modelling of overcurrent relay using digital signal processor - Goh Y.L.; Ramasamy A.K.; Abidin A.A.Z.; Nagi F.H. (2023)
Protective relays are used to detect any abnormalities in a power system and isolate the faulty section of the system in the shortest time, in order to minimize disturbances caused by failure in the system to ensure continuous power delivery. Protective relays for overcurrent protection are the most widely used relays in a power system. The implementation of overcurrent relay on digital signal processor (DSP) proficient to mitigate problems such as lack of memory capacity, lower speed and functionality, compared to conventional approach using microprocessor. The modelling of overcurrent relay for inverse definite minimum time (IDMT) type using DSP board TMS320F2812 will be discussed in the paper. Simulation results of the overcurrent relay from MATLAB/ Simulink and execution on TMS320F2812 will be presented. 2010 IEEE.